Rapid detection of t(15;17)(q24;q21) in acute promyelocytic leukaemia by microwave‐assisted fluorescence in situ hybridization. Issue 1 (2nd February 2015) - Soriani, Silvia; Mura, Cinzia; Panico, Anna Rita; Scarpa, Anna Maria; Recchimuzzo, Patrizia; Dadati, Raffaella; Farioli, Renata; De Canal, Gabriella; Mura, Maria Angela; Cesana, Clara
Abstract: Acute promyelocytic leukaemia (APL) is a hematologic malignancy characterized by the rearrangement of the PML and RARα genes, mostly due to a reciprocal chromosomal translocation t(15;17)(q24;q21). A quick APL diagnosis is essential for starting a prompt suitable therapy. We describe a new rapid diagnostic laboratory approach to detect the PML‐RARα rearrangement, which gives clear genetic results within 30 min of hybridization. It combines quick cell harvesting, fluorescence in situ hybridization performed with commercial DNA probe and microwave beams supplied by a domestic microwave oven. Copyright © 2015 John Wiley & Sons, Ltd.